Apoptotic depletion of CD4+ T cells in idiopathic CD4+ T lymphocytopenia. - Laurence, J (1996)
Progressive loss of CD4+ T lymphocytes, accompanied by opportunistic infections characteristic of the acquired immune deficiency syndrome, ahs been reported in the absence of any known etiology. The pathogenesis of this syndrome, a subset of idiopathic CD4+ T lymphocytopenia (ICL), is uncertain. We report that CD4+ T cells from seven of eight ICL patients underwent accelerated programmed cell death, a process facilitated by T cell receptor cross-linking. Apoptosis was associated with enhanced expression of Fas and Fas ligand in unstimulated cell populations, and partially inhibited by soluble anti-Fas mAb. In addition, apoptosis was suppressed by aurintricarboxylic acid, an inhibitor of calcium-dependent endonucleases and proteases, in cells from four of seven patients, The in vivo significance of these findings was supported by three factors: the absence of accelerated apoptosis in persons with stable, physiologic CD4 lymphopenia without clinical immune deficiency; detection of serum antihistone H2B autoantibodies, one consequence of DNA fragmentation, in some patients; and its selectivity, with apoptosis limited to the CD4 population in some, and occurring among CD8+ T cells predominantly in those individuals with marked depletion of both CD4+ T lymphocytes linked to clinical immune suppression have evidence for accelerated T cell apoptosis in vitro that may be pathophysiologic and amenable to therapy with apoptosis inhibitors.